"Here the snowman could live, but he missed everyone" Recognizing the life-philosophical dimension in a child's creative writing and aiding the child to develop - Tom Schoemaker (European Teacher Education Network, 2014)
In this article we analyse a short story, written by a child in sixth grade, to see what kind of life-philosophical dimensions can be recognized in it. Next we analyse the context in which the story was written, to see if we can extract more information about the child's ideas, but also to find what would be a good learning environment for a child to develop its own life philosophy. We end by formulating five tasks for a teacher if he wants to guide a child in developing its own life philosophy.